REFORMASI BIROKRASI PEMERINTAHAN DAERAH DALAM UPAYA PENINGKATAN PELAYANAN PUBLIK - Adnan, M. Fachri (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2013)
AbstractThis article discusses the importance of bureaucratic reform in order to improve public services in local government. There are several issues facing local governmentbureaucracy so that the bureaucracy has not been able to improve public services inlocal government including 1). Organizational structure and working procedures arenot efficient 2) community participation is still low, 3) transparency is not running, 4)the mechanism of action and tasks that is overlap 5) politicization of civil servants arestill symptomatic, 6) career system is not healty, 7) the bureaucratic apparatus are notwilling to respon the changing demands. So that, to solve the problems the localgovernment bureaucracy, should be reform which refers to the bureaucratic reformpolicy as outlined in the Grand Design bureaucratic reform at national level. In orde toprovide public services to community the local government has to have a minimumservice standards that are clear and measurable, and can be accessed quickly and easilyby the community. Key words: Bureaucracy, Reformation, Regional Government, Public Services AbstrakArtikel ini membahas tentang pentingnya reformasi birokrasi dalam rangka meningkatkan pelayanan publik di pemerintah daerah. Ada beberapa masalah yangdihadapi birokrasi pemerintah daerah sehingga birokrasi belum mampu meningkatkanpelayanan publik secara maksimal, diantaranya; 1 ) Struktur organisasi dan tata kerjayang tidak efisien, 2 ) partisipasi masyarakat masih rendah, 3 ) transparansi tidakberjalan, 4 ) mekanisme kerja dan tugas-tugas yang tumpang tindih 5 ) politisasipegawai negeri sipil masih gejala, 6 ) sistem karir tidak healty, 7 ) aparat birokrasi tidakbersedia respon tuntutan perubahan. Sehingga, untuk memecahkan masalah birokrasipemerintah daerah, harus dilakukan reformasi yang mengacu pada kebijakan reformasibirokrasi yang dituangkan Grand Design reformasi birokrasi yang ditetapkan padatingkat nasional. Dalam upaya memberikan pelayanan publik kepada masyarakatpemerintah daerah harus memiliki standar pelayanan minimum yang jelas dan terukur,dan dapat diakses dengan cepat dan mudah oleh masyarakat. Masyarakat juga dapatdapat menilai kualitas yang diberikan dengan menggunakan indek kepuasanmasyarakat. Kata kunci: Birokrasi, reformasi, pemerintahan daerah, pelayanan publik